Application of the Modified Early Warning Score by Nurse in Hospitals (Research, Society and Development, 2022)
Objective: to identify how the Modified Early Warning Score (MEWS) has been applied in hospital clinical practice by nurses. Method:  it is an integrative literature review; for the elaboration of the guiding question, the PICO strategy was used, as recommended by the Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA): The level of evidence of the selected studies was based on the Oxford Center for Evidence-based Medicine. Results: 24 articles were identified in the following sources: PUBMED, SCIELO, LILACS, SCOPUS and WEB OF SCIENCE; the levels of evidence were: 7 articles classified as 1A evidence; 12 articles rated 2A; 1 article rated 2A; 2 2C articles and 2 articles classified as 3A. The MEWS is applied as a predictor score for clinical deterioration of vital functions, in identifying the risk for the occurrence of cardiopulmonary arrest and establishing criteria for admission to the ICU. Conclusion: it was found that the use of MEWS in hospital clinical practice by nurses aims to assess the patient's health status, identifying signs of serious deterioration of vital functions. It supports the adoption of the principles of Patient Safety, in addition to favoring communication between the team, streamlines interventions by the Rapid Response Team.